Laparoscopic cholecystectomy for cholelithiasis in children - Gowda Deepak (Journal of Indian Association of Pediatric Surgeons, 2009)
Aim: To evaluate the role of laparoscopic cholecystectomy (LC) in the management of cholelithiasis in children. Methods: A retrospective review of our experience with LC for cholelithiasis at our institution, between April 2006 and November 2008, was done. Data included patient demographics, clinical history, hematological investigations, imaging studies, operative technique, postoperative complications, postoperative recovery, and final histopathological diagnosis. Results: During the study period of 32 months, 18 children (8 males and 10 females) with cholelithiasis were treated by LC. The mean age was 9.4 years (range 3-18). Seventeen children had symptoms of biliary tract disease and 1 child had incidentally detected cholelithiasis during an ultrasonography of abdomen for unrelated cause. Only 5 (27.8%) children had definitive etiological risk factors for cholelithiasis and the remaining 13 (75.2%) cases were idiopathic. Sixteen cases had pigmented gallstones and 2 had cholesterol gallstones. All the 18 patients underwent LC, 17 elective, and 1 emergency LC. The mean operative duration was 74.2 min (range 50-180). Postoperative complications occurred in 2 (11.1%) patients. The average duration of hospital stay was 4.1 days (range 3-6). Conclusion: Laparoscopic chloecystectomy is a safe and efficacious treatment for pediatric cholelithiasis. The cause for increased incidence of pediatric gallstones and their natural history needs to be further evaluated.